Comparative Efficacy of 5 Exercise Types on Cardiometabolic Health in Overweight and Obese Adults: A Systematic Review and Network Meta-Analysis of 81 Randomized Controlled Trials. Issue 6 (28th April 2022) - Batrakoulis, Alexios; Jamurtas, Athanasios Z.; Metsios, Georgios S.; Perivoliotis, Konstantinos; Liguori, Gary; Feito, Yuri; Riebe, Deborah; Thompson, Walter R.; Angelopoulos, Theodore J; Krustrup, Peter; Mohr, Magni; Draganidis, Dimitrios; et al.
Abstract : Background: Although regular exercise is recommended for preventing and treating overweight/obesity, the most effective exercise type for improving cardiometabolic health in individuals with overweight/obesity remains largely undecided. This network meta-analysis aimed to evaluate and rank the comparative efficacy of 5 exercise modalities on cardiometabolic health measures in individuals with overweight/obesity. Methods: A database search was conducted in MEDLINE, Embase, Scopus, and Web of Science from inception up to September 2020. The review focused on randomized controlled trials involving exercise interventions consisting of continuous endurance training, interval training, resistance training, combined aerobic and resistance training (combined training), and hybrid-type training. Exercise interventions aimed to improve somatometric variables, body composition, lipid metabolism, glucose control, blood pressure, cardiorespiratory fitness, and muscular strength. The Cochrane risk of bias tool was used to evaluate eligible studies. A random-effects network meta-analysis was performed within a frequentist framework. The intervention ranking was carried out using a Bayesian model where mean and SD were equal to the respective frequentist estimates. Results: A total of 4331 participants (59% female; mean age: 38.7±12.3 years) from 81 studies were included. Combined training was the most effective modality and hybrid-type training the second most effective in improving cardiometabolic health-related outcomes in these populations suggesting a higher efficacy for multicomponent exercise interventions compared to single-component modalities, that is, continuous endurance training, interval training, and resistance training. A subgroup analysis revealed that the effects from different exercise types were mediated by gender. Conclusions: These findings corroborate the latest guidelines on exercise for individuals with overweight/obesity highlighting the importance of a multicomponent exercise approach to improve cardiometabolic health. Physicians and healthcare professionals should consider prescribing multicomponent exercise interventions to adults with overweight/obesity to maximize clinical outcomes. Registration: URL: https://www.crd.york.ac.uk/PROSPERO/ ; Unique identifier: CRD42020202647